The comparison of preoxygenation methods before endotracheal intubation: a network meta-analysis of randomized trials - Zhong, Ming; Xia, Rong; Zhou, Junyu; Zhang, Jing; Yi, Xia; Yang, Anbo (Frontiers in Medicine, 2024)
Background Preoxygenation before endotracheal intubation (ETI) maintains asphyxiated oxygenation and reduces the risk of hypoxia-induced adverse events. Previous studies have compared various preoxygenation methods. However, network meta-analyses (NMAs) of the combined comparison of preoxygenation methods is still lacking. Methods We searched for studies published in PubMed, Embase, Web of Science, Scopus, and the Cochrane Library. Review Manager version 5.3 was used to evaluate the risk of bias. The primary outcome of this meta-analysis was low oxygen saturation (SpO2) during ETI. The secondary outcomes included SpO2 <80%, SpO2 <90%, and apnea time during ETI. NMA was performed using R 4.1.2 software gemtc packages in RStudio. Results A total of 15 randomized controlled trials were included in this study. Regarding the lowest SpO2, the noninvasive ventilation (NIV) with high-flow nasal cannula (HFNC) group performed better than the other groups. For SpO2 <80%, the NIV group (0.8603467) performed better than the HFNC (0.1373533) and conventional oxygen therapy (COT, 0.0023) groups, according to the surface under the cumulative ranking curve results. For SpO2 <90%, the NIV group (0.60932667) performed better than the HFNC (0.37888667) and COT (0.01178667) groups. With regard to apnea time, the HFNC group was superior to the COT group (mean difference: −50.05; 95% confidence interval: −90.01, −10.09; P = 0.01). Conclusion Network analysis revealed that NIV for preoxygenation achieved higher SpO2 levels than HFNC and COT and offered a more significant advantage in maintaining patient oxygenation during ETI. Patients experienced a longer apnea time after HFNC preoxygenation. The combination of NIV with HFNC proved to be significantly superior to other methods. Given the scarcity of such studies, further research is needed to evaluate its effectiveness. Systematic review registration identifier CRD42022346013